Aggregated carbon dots‐loaded macrophages treat sepsis by eliminating multidrug‐resistant bacteria and attenuating inflammation. Issue 1 (19th April 2022) - Li, Lihua; Chen, Lingling; Lu, Yao; Li, Binglin; Hu, Rong; Huang, Ling; Zhang, Tao; Wei, Xiaoming; Yang, Zhongmin; Mao, Chuanbin
Abstract: Sepsis, caused by uncontrollable infection and inflammatory response, leads to more than 30 million infected patients and results in high morbidity worldwide every year. Currently, no efficient approaches have been developed for sepsis therapy due to antimicrobial resistance and inflammatory storm. Here, we report macrophages loaded with aggregated carbon dots (ACDs) in the lysosome, termed MCDs, to treat sepsis in immunosuppressive mice. The ACDs are constructed by negative CDs and amine‐abundant polyethyleneimine (PEI), enabling them to bear the strong antibacterial ability and enhanced photoluminescent efficacy. The ACDs are specifically located in the macrophage lysosomes, efficiently enhancing the multidrug‐resistant bacteria‐killing ability of MCDs. More importantly, the MCDs possess superior anti‐inflammatory effects such as reducing the number of pro‐inflammatory (M1) and stimulating anti‐inflammatory (M2) macrophages. These effects upregulate the inflammatory cytokines (TNF‐α, IL‐1β, IL‐4, and IL‐10), ultimately resulting in increased sepsis survival. Our work provides an intelligent approach to overcoming multidrug‐resistant bacteria‐induced infection from sepsis patients and paves a new avenue on employing nanoparticle‐loaded cells for combating inflammation‐related infection. Abstract : Highly antibacterial and photoluminescent nanoparticles (ACDs), formed from carbon dots (CDs) and polyethyleneimine, are cocultured with macrophages to become localized at lysosomes. The resultant ACD‐loaded macrophages (MCDs) show a significantly enhanced multidrug‐resistant bacteria‐killing ability. They possess superior anti‐inflammatory effects, including inhibiting proinflammatory (M1) and stimulating anti‐inflammatory (M2) macrophages, therefore, improving the inflammatory cytokines and ultimately resulting in increased sepsis survival.